School-based multi-component intervention. Symptoms of Iranian ADHD children - Shaban, Sepideh; Baba, Maznah; Mohd Noah, Sidek; Wan Jaafar, Wan Marzuki (Canadian Center of Science and Education, 2015)
The present study evaluated the effectiveness of school-based multi-component intervention that implemented for ADHD school-aged children specially. Participants were 64 school-aged ADHD children that randomly assigned in two study groups including one experimental and one control group. Teachers of these children were invited to participate in the teacher training. Teachers took part in 8 sessions teacher training that involved contingency management, cognitive behavioral strategies and class management instructions for managing of ADHD children. Members of the control group didn’t receive any program. Dependent measures included parent and teacher`s ratings of inattention, hyperactivity/impulsivity and ADHD symptoms. Information for the study achieved in three pre-test, post-test and follow-up levels. Parents and teachers in experimental group reported significantly less inattention, hyperactivity/impulsivity symptoms in children at home and school respectively rather than before conducting the program. Findings of the study showed similar effect of school-based multi-component intervention on all symptoms of inattention, hyperactivity/impulsivity across home and school. Results of the present study provided some supports for effectiveness of school-based multi-component program on symptoms of ADHD in school-aged children in Iran.